Effect of Opposition Quality and Match Location on the Positional Demands of the 4-2-3-1 Formation in Elite Soccer - Giorgos Paraskevas; Ilias Smilios; Marios Hadjicharalambous (Proceedings, 2019)
AIM: The present study examined the influence of match location, quality of opposition team, and playing position on physical performance indicators of the 4-2-3-1 formation. MATERIAL & METHODS: Twenty-six games (with 184 player-observations and 17 players, who played the full 90 min) were recorded with a video system, and the physical demands of the players were analyzed according to their specific playing position (classified into wide defenders, central defenders, central midfielders, wide midfielders, and forwards). Match performance variables analyzed included total distance (TD), high-intensity running (HIR), very-high-intensity running (VHIR), and sprinting (SPR). RESULTS: There was a main effect of position on TD (F = 37.84, p < 0.001), HIR (F = 41.19, p < 0.001), VHIR (F = 27.89, p < 0.001), and SPR (F = 22.25, p < 0.001). Wide defenders covered the most SPR and—along with the central midfielders—the most VHIR. Central midfielders covered the most TD and HIR. Match location and opposition quality had interactive effects on TD (F = 12.96, p < 0.001), HIR (F = 8.33, p = 0.004) and VHIR (F = 8.17, p = 0.005). Competing against “weak” opponents, more TD, HIR, and VHIR were covered during home games compared to away games (p < 0.001). However, more TD was covered during away games against “strong” opponents compared to away games against “weak” opponents (p < 0.01). CONCLUSIONS: The current study supports more individualized specific intense-based drills (e.g., repeated sprint training) for wide defenders and more volume-based drills (e.g., long interval training) for central midfielders, whilst total weekly training load can be adjusted based on match location and quality of oppositions in the anticipated game-load.